2017
DOI: 10.1016/j.adolescence.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The immigrant paradox on internalizing symptoms among immigrant adolescents

Abstract: Understanding the immigrant paradox on health outcomes among UK's immigrant adolescents will greatly complement the research on immigrants that has already been established there by economists and interdisciplinary fields. This study used the first Longitudinal Study of Young People in England 2004e2010 database (N ¼ 15,770) to determine a) whether there was evidence of the immigrant paradox on internalizing mental health symptoms between first generation (n ¼ 753) and second plus generation (n ¼ 3042) 14/15 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…They include difficulties in learning Hebrew, understanding and managing the Israeli education system, getting one's professional credentials recognized, and finding a job in a relatively small Israeli job market (Amit, 2012;Bartram, 2011;Chachashvili-Bolotin, 2011;1 There is also a phenomenon called "the immigrant paradox" that relates to the following findings: 1) some groups of immigrants demonstrate less incidents of risky behavior (e.g., substance use, school truancy, and crimes) and have fewer health problems than the locals; 2) among some immigrant groups, time in the receiving country is positively correlated with social problems, and 3) second-generation immigrants may demonstrate more risky behavior than first-generation immigrants (Salas-Wright, Vaughn, Schwartz, & Córdova, 2016). However, the immigrant paradox was mostly found among adolescents, and it was not demonstrated regarding psychological well-being (Bowe, 2017). In addition, it was found mostly in the US, and its existence was rarely confirmed in Europe (Sam, Vedder, Liebkind, & Virta, 2008).…”
Section: Comparing Well-being In Immigrant and Non-immigrant Populationsmentioning
confidence: 99%
“…They include difficulties in learning Hebrew, understanding and managing the Israeli education system, getting one's professional credentials recognized, and finding a job in a relatively small Israeli job market (Amit, 2012;Bartram, 2011;Chachashvili-Bolotin, 2011;1 There is also a phenomenon called "the immigrant paradox" that relates to the following findings: 1) some groups of immigrants demonstrate less incidents of risky behavior (e.g., substance use, school truancy, and crimes) and have fewer health problems than the locals; 2) among some immigrant groups, time in the receiving country is positively correlated with social problems, and 3) second-generation immigrants may demonstrate more risky behavior than first-generation immigrants (Salas-Wright, Vaughn, Schwartz, & Córdova, 2016). However, the immigrant paradox was mostly found among adolescents, and it was not demonstrated regarding psychological well-being (Bowe, 2017). In addition, it was found mostly in the US, and its existence was rarely confirmed in Europe (Sam, Vedder, Liebkind, & Virta, 2008).…”
Section: Comparing Well-being In Immigrant and Non-immigrant Populationsmentioning
confidence: 99%
“…While these factors suggest that migrant youths should display relatively low levels of wellbeing, several studies have found the opposite (Cristini et al, 2015;Harker, 2001;Harris, 1999;Vaage et al, 2009). Terms such as the healthy migrant effect, and the immigrant paradox phenomenon (e.g., Bowe, 2017;Fuligni, 1998;Marks, Ejesi, & Garcia Coll, 2014), have been coined to capture this effect. There are many possible explanations.…”
Section: The Wellbeing Of Migrant Adolescentsmentioning
confidence: 99%
“…Terms such as the healthy migrant effect, and the immigrant paradox phenomenon (e.g., Bowe, 2017;Fuligni, 1998;Marks, Ejesi, & Garcia Coll, 2014), have been coined to capture this effect. There are many possible explanations.…”
Section: The Wellbeing Of Migrant Adolescentsmentioning
confidence: 99%
“…Conventional wisdom suggests that immigrants should exhibit more health problems given their high poverty rates, low education levels, less access to healthcare, and exposure to troubled neighborhoods (Cardoso & Thompson, 2010;Wright & Rodriguez, 2014;Ybarra, Ha, & Chang, 2017); yet, the opposite turns out to be true. Research in sociology, epidemiology, and public health has found immigrants to have lower rates of mental health problems, substance abuse, and eating disorders than U.S.-born individuals (Bowe, 2017;Ortega, Rosenheck, Alegría, & Desai, 2000;Salas-Wright et al, 2019). Research also shows that these paradoxical effects decline across generations, where firstgeneration immigrants are less likely to experience obesity, asthma, and poor health than second-or latergeneration individuals (Harris, 1999;Nguyen, 2006;Portes & Rumbaut, 2001).…”
Section: Incarceration Health and Immigrant Statusmentioning
confidence: 99%